ZONING DESIGN OF MARINE PROTECTED AREAS AS A TAPAL KUDA CONSERVATION EFFORT (INTERNATIONAL JOURNAL OF ANIMAL SCIENCE AND TECHNOLOGY RESEARCH AND DEVELOPMENT (IJASTRD), 2023)
The objectives to be achieved in this study are to map the potential of horseshoe crabs in Paleleh Sub-district, Buol Regency, Central Sulawesi Province, develop spatial planning for horseshoe crab conservation efforts in Paleleh sub-district, Buol Regency, Central Sulawesi Province and develop policies and strategies for water resources conservation. Paleleh sub-district, Buol district, Central Sulawesi province. Data and information search is to identify the potential of horseshoe crabs through secondary data and tabular data from various sources, including human resource data, infrastructure data and infrastructure data as well as the state of the marine environment. The activity of preparing the Spatial Planning of the Horseshoe Crab Conservation Area is carried out for 2 (two) months. Based on the results and analysis of the research, it can be concluded that PalelehSub district, Buol Regency has quite large fishery and marine resources with high biodiversity. These marine waters contain various types of pelagic fish and demersal fish (including reef fish), various non-fish marine biota (such as lobster, squid, clams and snails) as well as mangroves, karan and seagrass.